Systems and methods for checking and confirming the purchase of merchandise items - Susseelaa, Shangeetha Ravichandran; Sun, Yijing; Yuan, Mingquan; Reagan, Ryan B; Liu, Yao; Zhu, Feiyun; Wang, Zhenyu; Fang, Sicong; Zhang, Lingfeng; Mao, Tianyi; Xiao, Zhichun; Hammer, Jon; et al. (2025)
There are provided systems and methods relating to checking and confirming merchandise purchased at shopping facilities. In one form, the system includes: a shopping cart containing merchandise items to be purchased; a sales transaction database; a point-of-sales system that creates transaction records identified by transaction identifiers; and a mobile device used by an employee that includes a sensor to scan a paper or digital receipt to obtain the transaction identifier and a camera to capture images of the items in the shopping cart. The system also includes a control circuit that receives the transaction identifier, accesses the database using the identifier to determine the purchased items; analyzes the images of the merchandise items in the shopping cart and creates a computer vision receipt listing detected items; compares the purchased items with the detected items; and takes an action if there is a discrepancy.